An investigative study of remote eye tracker’s accuracy and precision in air traffic control environment - Ambrose, Vannesa Dionysius (2017)
Eye tracking technology has advanced over the past years and it serves as an important function in many experiments nowadays. Therefore, it is necessary for the researchers to know the actual accuracy and precision of the eye tracker before using the data for further analysis. Even though the eye tracker manufacturers may provide specification of the eye tracker, these accuracy and precision values are often obtained by doing the experiment in ideal conditions. However, in an actual experiment, it is often conducted in non-ideal conditions without fixing the participant’s head position. Therefore, there may be a deviation in the accuracy and precision of the eye tracker in actual experiment, in comparison with the specification stated by the manufacturer. Furthermore, there is a lack of research on accuracy and precision of eye tracker under non-ideal air traffic controller working environment. This project aims to investigate on how different head position affects the accuracy and precision of the eye tracker under non-ideal air traffic controller working conditions. The experiment will be conducted by asking the participants to focus on the 9 dots on the screen while varying different head position for different experimental runs. The data from each experiment runs will be collected and the accuracy and precision of the eye tracker for different head position will be tabulated Thereafter, an analysis on how different head position affects the eye tracker’s accuracy and precision is performed to identify the limitations of the eye tracker. Lastly, recommendations will be provided to improve accuracy and precision of the eye tracker for future similar experimental conditions.